THE CONCEPT OF LOVE IN COGNITIVE LINGUISTICS: A CONCEPTUAL AND METAPHORICAL APPROACH: THE CONCEPT OF LOVE IN COGNITIVE LINGUISTICS: A CONCEPTUAL AND METAPHORICAL APPROACH - Jadigerova, Aygul (Журнал иностранных языков и лингвистики, 2025)
Love is an emotionally intense, culturally significant, and cognitively complex human experience. It transcends time, language, and geography, and yet it is articulated and understood in diverse ways across cultures. From a cognitive linguistic standpoint, abstract concepts such as love are shaped and expressed through conceptual metaphors—mental mappings between domains of experience